OESTROGEN AND PROGESTERONE RECEPTORS’ EXPRESSION PATTERN IN FIBRO-ADENOMA OF THE FEMALE BREAST - Naeem, Shagufta; Shabana Naz; Khadija Amanullah; Hamza Javed; Omair Khan; Ehtesham Ahmed Khan Afridi; Sikandar Ahmed (Journal of Ayub Medical College Abbottabad, 2023)
Background: Fibro-adenoma is the most common benign condition of the female breast comprising about 68% of all breast lumps. Fibroadenoma is an independent risk factor for the development of breast cancer. Complex fibroadenoma has a 2-3-fold increased risk ratio and simple fibroadenoma has 1.49 times increased risk ratio of developing cancer than the normal population over a period of 20 years. This study aimed to qualitatively check the frequency of oestrogen receptor-positive and progesterone receptor-positive cases of fibroadenoma in our region. Methods: This cross-sectional study was conducted in the pathology department of Ayub Medical College, Abbottabad from June 2020 to December 2021. Biopsy confirmed cases of fibroadenoma were examined using immune-histochemical stains to score qualitatively the expression pattern of ER and PR. Data was analyzed and assessed using SPSS version 25. A p-value of ‰¤0.05 was considered statistically significant. Results: The mean age of patients who presented with fibro-adenoma was 24.5±9.29 years with a median age of 21.5 years. In most cases, oestrogen receptor expression was mild 23 (54.76%) whereas progesterone receptor expression was severe 19 (45.23%). On chi-square test, the pattern of progesterone receptor expression for the category of hormone intake showed significant differences. Whereas, the pattern of oestrogen receptor expression for the categories of marital status, history of hormone intake, history of menstrual cycle and type of fibroadenoma showed no statistically significant difference. Conclusion: Further study into the pathogenesis of fibroadenoma is required to understand the role of ER and PR and explore the therapeutic potential of such drugs that affects these receptors.